Pembiasaan Sholat Dhuha dalam Membangun Karakter Disiplin siswa - Khofi, Mohammad Bilutfikal (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This research aims to analyze the habituation of Dhuha prayer in building student discipline at MA ATQIA Bondowoso. Discipline is one of the essential aspects of character formation, particularly in time management, self-control, consistency, and responsibility. This study employed a qualitative method, with data collected through in-depth interviews, observation, and documentation. The findings reveal that the habituation of Dhuha prayer plays a vital role in improving time management, self-control, and adherence to school rules. Additionally, the program fosters respect and spiritual motivation, ultimately shaping students' disciplined and integrity-driven character. Therefore, the habituation of Dhuha prayer at MA ATQIA Bondowoso effectively shapes students' discipline in both academic and social contexts. Keywords: Dhuha Prayer; Discipline; Habituation; Character Education; Character Building